Taxillus Thibetensis (Lecomte) Danser (Loranthaceae) a New Record Species For Flora of Vietnam - Le, Chi Toan; Nguyen, Van Du; Pham, Thu Lan; Le, Thi Ngat; Liu, Bing (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2DO - 10.25073/2588-1140/vnunst.5126, 2021)
Taxillus thibetensis (Lecomte) Danser (Loranthaceae), a species previously known only from China, is newly recorded from Vietnam. A specimen discovered in the rainforest of Lao Cai province, Northern Vietnam was identified as Taxillus thibetensis based on both morphological and molecular data. The Vietnamese individuals of Taxillus thibetensis are closely related to T. thibetensis in China. A detailed description,  illustration and data on distribution, ecology, phenology of Vietnamese Taxillus thibetensis are provided